Traditions and Myths of Kajang People in South Sulawesi - Anggraini, Lya Dewi (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to elaborate the myths following traditions in explicit connection with the Kajang indigenous people's dwellings and way of life. The existence of Kajang indigenous people was known for preserving their traditions with austerity. Clinging to their traditional belief system, Pasang ri Kajang was used to protect their sacred forest and natural environment. Some myths still seemed relevant and took part actively in their everyday lives. This was an empirical qualitative research, with the researcher directly visiting the location to experience the cultural situation and the people of Kajang. First-hand experience, photographing, hand sketching, interviews, and focus group discussions were employed to collect data. Analyzing the characteristics of the Kajang area from the maps, narrative analysis for the interview, focus group discussion, sketches, manual notes, photographs, and cross-analysis from literature studies resulted in the difference between inner and outer Kajang. It is found that eight practical conducts closely related to the myths are elaborated, such as oral communication, no electricity, no clay roof tile, no footwear, no colorful clothes, no decoration or modern material, orientation of buildings, and odd numbering and time calculation. Some limitations and suggestions are also presented.Â